Development of Teaching Materials Containing Local Wisdom in Drama Appreciation Material - Shofi, Moh Shofiuddin; Wakhyudi, Yukhsan; Nurika Irma, Cintya; Khoeriyah, Saniatul; QaolanSyadida, Liza (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aim of this study is to determine the feasibility of using a learning media containing local wisdom for drama appreciation material for students of the Indonesian Language Education Study Program. The development of the web-based learning medium uses the ADDIE development model. The implementation of this research is limited to the Development stage. Based on the assessment by three validators, the average score obtained was 79%. This indicates that the learning medium, which incorporates local wisdom in drama appreciation materials, is considered feasible for use. This is based on the assessments from three validators: a content validator (71%), a media validator (75%), and a language validator (92%).